Features of the development of Ukraine's foreign economic activity under conditions of a full-scale war - Kolosov, Serhii; Mokhammad, Ramin; Telebienieva, Ievgeniia (Human Geography Journal, 2026)
The article analyzes the development of Ukraine's foreign economic activity under conditions of a full-scale war in 2024–2025. The main trends in foreign trade in goods are examined, in particular the dynamics of exports and imports, changes in their commodity and geographical structure, as well as the transformation of the country's role in international trade chains. It is established that trade operates under conditions of increased risk due to security threats, destruction of production and logistics infrastructure, and the restructuring of traditional sales markets. It is demonstrated that, despite the preservation of significant export potential, primarily in the agricultural sector, metallurgy, and the food industry, the import dependence of the economy is increasing. This is due to the need for energy resources, machinery, equipment, transport, and defense-related goods.As a result, a persistent trade deficit is formed, reflecting military expenditures and structural imbalances in the economy. Particular attention is paid to changes in the geographical structure of trade, in particular the growing role of the EU as a key partner and the reorientation of export flows toward alternative routes. The functioning of the maritime corridor is identified as an important factor in stabilizing exports. Gradual changes in exports are also identified, namely the emergence of niche products with higher added value, although the raw material orientation still dominates. At the same time, these processes are accompanied by rising logistics costs and the need for enterprises to adapt to new conditions of international trade. It is concluded that Ukraine’s foreign trade model is transitional in nature, dependent on external factors, and requires transformation toward increasing the added value of exports, diversifying markets, and enhancing economic resilience.